(untitled) - Betul Tosun; Nursemin Unal; Serap Gungor; İsmail Dusak; Canan Porucu; Ayla Yava (University of Ostrava, 2022)
Aim: The aim of the study was to evaluate nursesʼ knowledge of protective precautions and their experiences of various factors during the Covid-19 pandemic. Design: A descriptive cross-sectional study. Methods: In this descriptive cross-sectional study, the snowball method was selected for sampling to access nurses (n = 392) serving in the fight against the Covid-19 infection nationwide. The online data collection form had two parts: a sociodemographic form and a second part including 25 items on institutional protective measures, personal protective measures, and nursing care. Results: Most of the nurses caring for patients with Covid-19 were well-informed about institutional, personal, and patient protective precautions. The scores of female nurses, married nurses and those with children were higher. Multiple regression analysis revealed that in-service training, working in a clinic, and having colleagues diagnosed with Covid-19 positively affected knowledge, while having 0-5 years of professional experience negatively affected knowledge. Conclusion: This study may enlighten medical authorities and policymakers in their efforts to promote the quality of care delivered to patients with Covid-19 and the quality of working conditions of healthcare providers.